Provenance Trial on Eucalyptus cloeziana in Western Ghats of Karnataka, India - Manaturagimath, B. B.; Bulgannawar, G. N.; Parameswarappa, S.; Burley, J. (Indian Forester, 1991)
Eucalyptus is one of the most ubiquitous trees and is of great importance in developing countries aS a source of raw-material for firewood and wood based industries. Early growth performance of five different provenances of Eucalyptus cloeziana was studied in a high rainfall zone of Western Ghats of India, which receives 2000 mm to 3500 mm of rainfall annually. The height, DBH, volume and survival percentage of these provenances at various ages were studied for five years. The North-West of Cardwell QLD, provenance, has sbowed the best performance in height, DBH and volume followed by South East of Gymple QLD, then by 8 km South of Helenvale QLD, tbe North-West of Cooktown QLD and finally by 26 km South-West of Monto QLD. So far, no pests and diseases were observed in the trial plot.